Mapeamento semântico do turismo sustentável (arquitetando um novo país) - Oliveira, Luciano Amaral (Boletim Técnico do Senac, 2004)
An analysis of the theoretical implications of sustainable tourism based on its semantic imbrications. The text sets out to verify whether sustainable tourism can help to shape a new country both from the geophysical and socio-cultural point of view. This type of analysis is needed at a time when people are traveling more and more in search of natural destinations and theoreticians are being driven further apart by the vagueness of concepts.